A Radiologic Review of Visceral Artery Aneurysms. (15th July 2017) - Chen, Brandon; Sung, Chris; Rambhia, Suraj; Kwak, No Bong
Abstract : Visceral artery aneurysms are rare, with a historical prevalence of 0.1% to 2% during autopsy.1, 2 However, more visceral artery aneurysms are being identified in practice. This is the result of biliary tract instrumentation, arterial catheterization for local regional treatment of hepatic malignancies, liver transplantation, and incidental findings from the widespread use of abdominal imaging.1